2020
DOI: 10.3390/jcm9113565
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Prescription of Non-Vitamin K Antagonist Oral Anticoagulants for Atrial Fibrillation: Results of the Polish Atrial Fibrillation (POL-AF) Registry

Abstract: Background: Current guidelines do not suggest in which groups of patients with atrial fibrillation (AF) individual non-vitamin K antagonist oral anticoagulants (NOACs) should be used for the prevention of thromboembolic complications. The aim of this study was to evaluate the frequency of use of apixaban, dabigatran, and rivaroxaban, and attempt to identify factors predisposing their administration. Methods: The Polish Atrial Fibrillation (POL-AF) registry is a prospective, non-interventional study, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
(46 reference statements)
0
9
0
1
Order By: Relevance
“…The analysis was carried out on a group of patients from the Polish Atrial Fibrillation (POL-AF) registry. The methodology has been previously described in detail [9,10]. The POL-AF registry is a prospective, observational, multicenter study.…”
Section: Patientsmentioning
confidence: 99%
“…The analysis was carried out on a group of patients from the Polish Atrial Fibrillation (POL-AF) registry. The methodology has been previously described in detail [9,10]. The POL-AF registry is a prospective, observational, multicenter study.…”
Section: Patientsmentioning
confidence: 99%
“…A similar trend was also noted in the 2017-2018 analysis of other European populations [40], as well as in the population of Central Europe, which is represented by the Poles. In 2019, in a large Polish registry, 84% of patients with AF were treated with NOACs [41]. Confirming the validity of the findings from the registries and subsequent randomized data, the 2020 recommendations for the management of patients with AF unequivocally indicate that NOACs should be the preferred group of drugs for antithrombotic prophylaxis [17].…”
Section: Discussionmentioning
confidence: 96%
“…The POL-AF Registry (NCT04419012) was a prospective, observational study enrolling AF patients hospitalized in 10 cardiology departments (eight academic centers and two territorial centers) in Poland. Details on the study design and main results have been reported elsewhere [5,6]. Briefly, consecutive hospitalized patients in cardiology centers diagnosed with AF, except those admitted for AF ablation (in centers with electrotherapy labs), were included in the registry.…”
Section: Study Populationmentioning
confidence: 99%